Compendium of plants used for preparation of traditional alcoholic beverages by four major ethnic communities of Assam, northeast India - Dipankar Borah; TRIDIP GOGOI; JINTU SARMA; PUNAM JYOTI BORAH; BICHITRA GOHAIN; CHIRANJIB MILI; ANKUR UPADHYAYA; JENIMA BASUMATARY; KASTURI NEOG; TONLONG WANGPAN; SUMPAM TANGJANG (Society for Indonesian Biodiversity, 2021)
Abstract. Borah D, Gogoi T, Sarma J, Borah PJ, Gohain B, Mili C, Upadhyaya A, Basumatary J, Neog K, Wangpan T, Tangjang S. 2021. Compendium of plants used for preparation of traditional alcoholic beverages by different major ethnic communities of Assam, Northeast India. Biodiversitas 22: 2019-2031. This paper deals with the ethnobotanical research on the preparation of traditional alcoholic beverages by Ahom, Bodo, Karbi and Mishing ethnic communities of Assam, India. Along with the information on preparation, the plant species associated with the preparation of alcoholic beverages are also recorded. Field investigations were conducted to cover 32 villages of six districts of Assam, India. The data was generated from 202 respondents using participatory rural appraisal tools including semi-structured questionnaires and personal interviews. The plant species were collected, identified and submitted in the Herbarium of Rajiv Gandhi University, Arunachal Pradesh, India. The study recorded 129 plants falling under 107 genera and 54 families which are exclusively used for the preparation of alcoholic beverages by the studied communities. The study confirmed that the association of traditional alcoholic beverages with their rich indigenous knowledge.. The finding also revealed varied forms of protocol followed by these tribes to prepare traditional liquors and the starter cakes for brewing of alcohol were prepared locally. However, the Mishing tribe was known to prepare unique rice beer known as Po:ro apong, as the preparation technique and extraction process of this liquor was slightly different. Distillation of alcohol was also observed in all the communities except the Ahom. The rich traditional knowledge of brewing alcohol and the plant species used in the process were worth documenting considering the on-going alteration of traditional society with the modernization.